Eschatology, the Elimination of Evil, and the Ontology of Time - Hollingsworth, Andrew (TheoLogica: An International Journal for Philosophy of Religion and Philosophical Theology, 2024)
Part and parcel of the eschatology of the three Abrahamic faiths is the belief that sin and evil will be eliminated upon the consummation of God’s kingdom on earth. Not only do these beliefs affirm that God will ultimately “deal” with the problem of sin and evil, but that sin and evil will be no more. I refer to this eschatological belief as “the elimination of evil” (EOE). The EOE has important implications for how one understands the ontology of time. In this paper, I contribute to this discussion by arguing that ontologies of time that affirm the concrete existence of past moments are incompatible with the EOE. I also argue that solutions based on theories of hypertime, such as those posited by Tyron Goldschmidt and Samuel Lebens, also fail to solve the problems posed to those ontologies of time affirming the concrete existence of the past. I conclude that the ontology of time that best facilitates the EOE is presentism.